Reka bentuk kasut sepak takraw - Soovirehn, a/l Epeng (Universiti Malaysia Sarawak (UNIMAS), 2014)
Sepak takraw shoes design study, aim to study and analyse shoes design that is effective to every players position. Method used is shaped descriptive which use questionnaire method to get information from aspect of design, colour and ergonomics factor in shoes design. Experimentation method also be carried out to know material suitability from texture perspective and resilience. Takraw shoes produced have three design set that are different per players position. Researcher hope so that this design proposal able to contribute level of play that is more effective.